2009
DOI: 10.1053/j.ajkd.2009.01.264
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of GFR-Estimating Equations Following Kidney Donation

Abstract: Background-It is not clear which serum creatinine-based glomerular filtration rate (GFR) estimating model performs best in kidney donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…Long-term observation of transplant kidney donors suggested that the remaining kidney would compensate adequately. 8 However, renal cancer patients are typically older than the average living transplant donor. They also have underlying chronic illnesses and an increased rate of CKD, and they are less able to accommodate removal of one kidney.…”
Section: Radical Nephrectomy Is Too Radicalmentioning
confidence: 99%
“…Long-term observation of transplant kidney donors suggested that the remaining kidney would compensate adequately. 8 However, renal cancer patients are typically older than the average living transplant donor. They also have underlying chronic illnesses and an increased rate of CKD, and they are less able to accommodate removal of one kidney.…”
Section: Radical Nephrectomy Is Too Radicalmentioning
confidence: 99%
“…reported on the performance of these equations in a large cohort of living kidney donors who underwent formal iohexol glomerular filtration rate (mGFR) measurement and found that the re-expressed Modification of Diet in Renal Disease (MDRD) equation could be a reasonable substitute, albeit still suboptimal and is clearly inferior to formal GFR measurements (7,8).…”
mentioning
confidence: 99%
“…Watnick (13) found the mean GFR of 66 ml/min per 1.73 m 2 measured by inulin clearance in 29 donors with similar ages and intervals after donation to our Caucasian donor group. In a more recently published study from Minnesota, a subgroup of subjects had GFR measured by plasma disappearance of iohexol (16). Compared with donors in this series, our control group of Caucasian donors had higher measured GFR (78.2 ml/min versus 71.8 ml/min), although the interval from donation was very similar (12 Ϯ 4 years for our series versus 12 Ϯ 9 years for Minnesota donors).…”
Section: Discussionmentioning
confidence: 47%
“…Self-reported prevalence of HTN in Caucasian donors was 24.7% (16). Our study indicates that HTN, although more prevalent in the AA than Caucasian general population with two kidneys, is less prevalent in AAs than Caucasians with 50% reduction in kidney mass.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation